Optic Nerve Sheath Meningioma Masquerading as Optic Neuritis. (19th January 2016) - Alroughani, R.; Behbehani, R.
Abstract : Optic neuritis is a common presentation of demyelinating disorders such as multiple sclerosis. It typically presents with acute painful monocular vision loss, whereas chronic optic neuropathy can be caused by compressive lesions along the anterior visual pathway, genetic, toxic, or nutritional causes. We report an unusual presentation mimicking optic neuritis, which was subsequently diagnosed as optic nerve sheath meningioma (ONSM). Misinterpretation of white matter lesions on MRI of brain and the failure to image the optic nerves at the time of acute loss of vision led to the misdiagnosis of optic neuritis in this case. A comprehensive accurate history and ordering the appropriate imaging modality remain paramount in diagnosing progressive visual deterioration.